2022
DOI: 10.1002/ptr.7491
|View full text |Cite
|
Sign up to set email alerts
|

Nutmeg (Myristica fragrans Houtt.) essential oil: A review on its composition, biological, and pharmacological activities

Abstract: Myristica fragrans (Houtt.) is an evergreen tree native to the Maluku Islands, Indonesia. M. fragrans kernel is extensively used in Indian traditional medicines to treat various diseases. Several studies attempt to compile and interpret the pharmacological potential of Myristica fragrans (Houtt.) aqueous and various chemical extracts. Thus, the pharmacological potential of nutmeg essential oil has not been reviewed phytochemically and pharmacologically. Therefore, the present study aimed to share appropriate l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 60 publications
1
26
0
Order By: Relevance
“…Compared with other studies, it was found that Myristica fragrans Houtt. essential oil yield prepared using hydrodistillation was from 3.2% to 10.3% and when prepared by steam distillation was 0.3–12.5% [ 10 ]. The essential oil isolated from the seeds of Myristica fragrans Houtt.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared with other studies, it was found that Myristica fragrans Houtt. essential oil yield prepared using hydrodistillation was from 3.2% to 10.3% and when prepared by steam distillation was 0.3–12.5% [ 10 ]. The essential oil isolated from the seeds of Myristica fragrans Houtt.…”
Section: Resultsmentioning
confidence: 99%
“…Botanical substances obtained from plants, such as Trifolium pratense L. flowers, Glycyrrhiza glabra L. roots, and Myristica fragrans Houtt. essential oil, which are generally perceived as safe because of their natural origin, can be used for the prevention or treatment of menopausal health issues, various degenerative disorders, and possess many pharmacological activities, such as antiviral, antimicrobial, anti-inflammatory, antitumor, and other activities [ 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. These plant substances could act synergistically and increase positive effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eugenol, a naturally occurring compound, has been reported to be present in several plant families including Holy basil or tulsi leaves ( Lamiaceae ), Eugenia caryophyllata (clove) [ 10 ], Zingiber officinale (ginger) [ 11 ], bark and leaves of Cinnamomum verum (cinnamon) [ 12 ], Curcuma longa (turmeric) [ 13 ], as well as various aromatic plants such as Ocimum basilicum (basil) [ 14 ], Myristica fragrans (Houtt.) (nutmeg) [ 15 ], and Cinnamomum loureiroi Nees. (Saigon cinnamon) [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nutmeg is the tough kernel of an evergreen tree's seed. Steam distillation of pulverized nutmeg yields an essential oil widely used in the fragrance and medicinal sectors [1][2][3]. The essential oil is colorless or pale yellow in color, smells and tastes like ground nutmeg.…”
Section: Introductionmentioning
confidence: 99%